Partisipasi Citizen Journalism dalam Mengembangkan Informasi Seni Ketangkasan Domba Garut - Tannia Meirina Anwar; Atie Rachmiatie (Bandung Conference Series: Journalism, 2023)
Abstract.This research is motivated by citizen journalism or known as Citizen journalism has an active role in the process of collecting, reporting, analyzing, and disseminating news and information owned. The purpose of this study was to determine the contribution, role, and expectations of citizen journalism in the development of Sundanese cultural information, the art of dexterity of the Garut sheep on social media Instagram. This relates to the nature of humanity that needs and is accustomed to telling "story" to others. Today's culture has a lot of acculturation and many foreign cultures come. As many cultures enter, people begin to forget about it. Garut Sheep Dexterity Art which has begun to dim and is almost extinct. With the help of citizen journalism Through social media Instagram, friendship and friendship then become very easy to access, this cultural art is starting to be spread again and it can be said that this culture has increased in level from previous years. Not only in Garut, this art has also spread to several cities, for example: Bandung, Sumedang, Bogor, Tasikmalaya. This research uses a qualitative method with an explanatory case study approach. By using interview data collection techniques with informants and administrators of HPDKI (Indonesian Goat Sheep Breeders Association), observation, and content analysis or Instagram content about the art of garut sheep agility. The results of the study found that citizen journalism has an important role in developing information on the art of garut sheep agility on Instagram social media. It's just that there has been no more contribution for HPDKI or the Indonesian Sheep Goat Breeders Association as the organization that houses the art of arrowroot sheep agility. Abstrak. Penelitian ini dilatar belakangi oleh citizen journalism atau dikenal dengan Jurnalisme Warga mempunyai peran aktif dalam proses pengumpulan, pelaporan, analisis, dan menyebarkan berita serta informasi yang dimiliki. Tujuan penelitian ini dilakukan untuk mengetahui kontribusi, peran, dan harapan citizen journalism dalam pengembangan informasi budaya sunda seni ketangkasan domba garut di media sosial Instagram. Hal ini berkaitan dengan sifat kemanusiaan yang membutuhkan dan terbiasa menyampaikan “kisah” kepada sesama. Kebudayaan saat ini telah banyak akulturasi dan banyak budaya asing berdatangan. Seiring banyaknya budaya yang masuk, masyarakat pun mulai melupainya. Seni Ketangkasan Domba Garut yang sudah mulai redup dan hampir punah. Dengan dibantu oleh citizen journalism Melalui sosial media Instagram, maka perkawanan dan persahabatan lalu menjadi sangat mudah untuk diakses, Seni kebudayaan ini pun mulai terjamak lagi dan dapat dikatakan bahwa budaya ini naik tingkatannya dari taun taun sebelumnya.Tak hanya di Garut, kesenian ini pun sudah menyebar ke beberapa kota, contohnya: Bandung, Sumedang, Bogor, Tasikmalaya. Penelitian ini memakai metode kualitatif dengan pendekatan studi kasus eksplanatoris. Dengan menggunakan teknik pengumpulan data wawancara dengan informan dan pengurus HPDKI (Himpunan Peternak Domba Kambing Indonesia), observasi, serta analisis isi atau konten Instagram tentang seni ketangkasan domba garut. Hasil penelitian menemukan bahwa citizen journalism memiliki peran penting dalam pengembangan infomasi seni ketangkasan domba garut di media social Instagram. Hanya saja belum ada kontribusi lebih untuk HPDKI atau Himpunan Peternak Domba Kambing Indonesia selaku organisasi yang menaungi seni ketangkasan domba garut.